Self-Assessment of the Intercultural Competences of Medical Doctors and Nurses in Poland in the Face of Current Refugee Challenges - Freund, Bożena (Acta Universitatis Lodziensis. Folia Oeconomica, 2024)
Health care is one of the most important systems in both society and the economy. At the same time, it is a highly complex system that is subject to an increasing number of challenges in the contemporary world. For example, the health care system in Poland struggles primarily with inadequate numbers of nurses and medical doctors, as well as insufficient funding. A relatively new challenge is to provide for the health needs of refugees, whose number is increasing due to the war in Ukraine beyond Poland’s eastern border. This raises the question of the substantive preparation of nurses and medical doctors to work in a culturally diverse environment. Have they had the opportunity to train in intercultural competences? How do they assess their own intercultural competences? Do they see challenges in their interactions with foreigners? The aim of this paper is therefore to present a self‑assessment of the intercultural competences of medical doctors and nurses in Poland, in particular in the context of current refugee challenges. In order to achieve the assumed goal, a proprietary questionnaire form was created, and a nationwide survey was conducted among a group of professionally active medical doctors and nurses. The results of the research, in addition to providing valuable knowledge, were used to draw up specific recommendations for improving the continuing education of medical and nursing staff in the area of intercultural competences. Based on the research results, guidelines for better management in public health organisations were also created. This text may be of interest to researchers of management in public health care organisations, and in particular human resources management in health care institutions, as well as practitioners trying to deal with the current problems facing public health management.